Attitudes towards Euthanasia among physicians and patients: a cross sectional survey from Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Mohd Shah, Azarisman Shah; Omar, Ahmad Marzuki; Osman, Ariff (Eubios Ethics Institute, 2010)
Introduction: The term euthanasia or Mercy killing is in essence the termination of life of a terminally ill patient at his request or in his interest. Due to increase in ageing population with extremely limited physical and mental capacities, the issue is being discussed in a number of jurisdictions in favour of its legalization. However there is intense public debate and controversy among its proponents and opponents. The controversy regarding its practice is essentially a controversy about ethics and morality. Virtually all of the research in this field has been with Western, largely Christian, populations. There is a pressing need for more cross-cultural, international collaborative studies on the subject. Aim of the study: The present ongoing study has some promise since it samples a population of patients and physicians who are multi-racial and multi-faith. We want to ascertain the prevalent beliefs and views among patients and physicians in Malaysia. Concomitantly we want to ascertain the frequency of requests for assistance in active euthanasia. Methods: Trained research assistant administered questionnaire to a convenience sample of consenting patients and physicians. The influence of a number of independent variables such as cultural and religious beliefs, age and gender will also be investigated, as it is believed that they have a great influence on most individualsʼ attitudes towards euthanasia. A cross-cultural perspective and attitude towards euthanasia could enrich our understanding and thus provide insights for societal stability. The interim results of our findings: The majority of patients were male (62.9%), Malay Muslims (75.4%) and had primary (32.5%) or secondary (48.6%) education. Nearly all patients and doctors believed in the existence of God and life after death. Only a quarter of physicians agreed with euthanasia, while among patients only 6.4% agreed with euthanasia and 92% had a hope of cure. The full paper along with final results will be published once the study is complete.